Impact of baseline left ventricular ejection fraction on outcome after transfemoral transcatheter aortic valve implantation in patients with and without low‐gradient aortic stenosis. Issue 1 (28th November 2018) - El‐Chilali, Karim; Patsalis, Polykarpos Christos; Al‐Rashid, Fadi; Kahlert, Heike Annelie; Riebisch, Matthias; Mincu, Raluca‐Ileana; Totzeck, Matthias; Lind, Alexander; Jánosi, Rolf Alexander; Kehren, Clemens; Dirkmann, Daniel; Peters, Jürgen; et al.
Abstract : Objectives: To evaluate the impact of baseline left ventricular ejection fraction (LVEF) and its interaction with low‐gradient aortic stenosis (LGAS) on all‐cause mortality after transfemoral aortic valve implantation (TF‐TAVI). Methods: We reviewed mortality data of 624 consecutive single center TF‐TAVI patients and categorized LVEF according to current ASE/EACVI recommendations (normal, mildly‐, moderately‐, and severely abnormal). Results: Baseline LVEF was normal in 336 (53.8%), mildly abnormal in 160 (25.6%), moderately abnormal in 91 (14.6%), and severely abnormal in 37 (5.9%) patients, and 1‐year mortality was 19%, 17%, 23%, and 43% ( P  = 0.002), respectively. Patients with LGAS had a similar 1‐year mortality compared to those without LGAS in groups with normal (19% vs 19%, P  = 0.899) and mildly abnormal LVEF (16% vs 17%, P  = 0.898). One‐year mortality of patients with LGAS was significantly greater than in those without LGAS in presence of moderately abnormal LVEF (31% vs 11%, P  = 0.022), and it was numerically greater than in those without LGAS in presence of severely abnormal LVEF (48% vs 25%, P  = 0.219). In multivariate analysis, only the combination of moderately/severely abnormal LVEF and LGAS predicted increased 1‐year mortality (HR: 2.12, 95% CI: 1.4–3.2, P  < 0.001). Other variables, including EuroSCORE I did not affect this result. Conclusions: Moderately/severely abnormal LVEF (≤40%) at baseline is associated with increased mortality after TF‐TAVI, especially when the mean transvalvular aortic gradient is <40 mm Hg (LGAS), while outcomes in patients with normal and mildly abnormal LVEF are comparable regardless of the pressure gradient across the native aortic valve. (DRKS00013729).